Celastrol directly binds with VAMP7 and RAB7 to inhibit autophagy and induce apoptosis in preadipocytes - Liu, Chenshu; Li, Na; Peng, Meixiu; Huang, Kan; Fan, Dongxiao; Zhao, Zhengde; Huang, Xiuyi; Liu, Yunchong; Chen, Sifan; Li, Zilun (Frontiers in Pharmacology, 2023)
Obesity is one of the most prevalent chronic metabolic diseases, and induction of apoptosis in preadipocytes and adipocytes is a potential strategy to treat obesity. Celastrol represents one of the most robust anti-obesity phytochemicals so far, yet its direct binding target remains elusive. Here, we determined that celastrol could induce apoptosis in preadipocytes via mitochondrial mediated pathway. Further study clarified that celastrol inhibited the fusion of autophagosome and lysosome to prohibit autophagy, leading to cell apoptosis. By conducting virtual screening and genetic manipulation, we verified that overexpression of VAMP7 and RAB7 could block the effects of celastrol on inhibiting autophagy and inducing apoptosis. The Surface Plasmon Resonance study confirmed the direct binding of celastrol with VAMP7 and RAB7. The functional study illustrated the inhibition of RAB7 GTPase activity after celastrol treatment. Moreover, celastrol induced comparable apoptosis in murine epididymal adipose tissue, human preadipocytes and adipocytes, but not in human hepatocytes. An inhibitory effect on differentiation of human primary visceral preadipocytes was also observed. In conclusion, celastrol exhibited inhibitory effect of autophagy via direct binding with VAMP7 and RAB7, leading to an increase in preadipocytes apoptosis. These results advance our understanding in the potential application of celastrol in treating obesity.